2012
DOI: 10.1590/s1677-55382012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele among healthy young men in Turkey; prevalence and relationship with body mass index

Abstract: ARTICLE INFO _______________________________________________________________ _____________________

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 21 publications
0
39
0
1
Order By: Relevance
“…Handel et al [3] reported that the prevalence of varicocele decreases with increasing BMI because of increased adipose tissue, which decreases compression of the left renal vein. However, Delaney et al [4] reported that patients with varicoceles were taller, but contrary to the previous reports [11], they were heavier and BMI was not significantly different compared with respective growth charts for boys aged 2 to 20 years. They hypothesized that taller individuals were more susceptible to increased hydrostatic pressure owing to the increased length required for drainage of the spermatic vein.…”
Section: Discussionmentioning
confidence: 81%
“…Handel et al [3] reported that the prevalence of varicocele decreases with increasing BMI because of increased adipose tissue, which decreases compression of the left renal vein. However, Delaney et al [4] reported that patients with varicoceles were taller, but contrary to the previous reports [11], they were heavier and BMI was not significantly different compared with respective growth charts for boys aged 2 to 20 years. They hypothesized that taller individuals were more susceptible to increased hydrostatic pressure owing to the increased length required for drainage of the spermatic vein.…”
Section: Discussionmentioning
confidence: 81%
“…In 12 studies: first, no significant differences in BMI were detected (Delaney et al, 2004;Kilic et al, 2007), secondly, patients with varicocoele had a distinctly lower BMI (May et al, 2006;Baek et al, 2011), and thirdly, the number of the varicocoele patients decreased as the BMI increased, as found by others (Handel et al, 2006;Nielsen et al, 2006;Prabakaran et al, 2006;Kumanov et al, 2008;Tsao et al, 2009;Al-Ali et al, 2010;Chen & Huang, 2010;Hassanzadeh et al, 2011;Soylemez et al, 2012) and us. It is clear that obesity may lead to decreased detection of varicocoele, even in our study, because of difficulty in palpation on physical examination.…”
Section: Discussionmentioning
confidence: 81%
“…In the literature; there are 14 articles in which the relationship of Soylemez et al, 2012). Of 14 studies, nine investigated the relationship between height and varicocoele.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is decreased detection due to adipose tissue in the spermatic cord. The decrease in varicocele prevalence as a function of BMI regardless of varicocele grade suggests this explanation is less likely [16]. Celiktas M, and associates have shown a decreases in varicocele incidence in obese men due to the increased retroperitoneal fat thickness and the adipose tissue deposition within the inguinal cord structures and scrotal content [17].…”
Section: Commentarymentioning
confidence: 99%